Effect of bacterial LPS, poly I:C and temperature on the immune response of coelomocytes in short term cultures of red sea urchin (Loxechinus albus). Issue 107 (December 2020) - Dettleff, Phillip; Villagra, Maximiliano; González, Joaquín; Fuentes, Marcia; Estrada, Juan Manuel; Valenzuela, Cristian; Molina, Alfredo; Valdés, Juan Antonio
Abstract: In echinoderms, the immune system plays a relevant role in defense against infection by pathogens. Particularly, in sea urchins, the immune system has been shown to be complex, especially in terms of the variety of immune genes and molecules described. A key component of the response to external pathogens are the Toll-like receptors (TLRs), which are a well-characterized class of pattern recognition receptors (PRRs) that participate in the recognition of pathogen-associated molecular patterns (PAMPs). Despite the fact that TLRs have been described in several sea urchin species, for the red sea urchin ( Loxechinus albus ), which is one of the most important sea urchins across the world in terms of fisheries, limited information on the TLR-mediated immune response exists. In the present study, for the first time, we evaluated the effect of thermal stress, LPS and poly I:C treatment on the coelomocyte immune response of Loxechinus albus to determine how these factors modulate TLR and strongylocin (antimicrobial peptides of echinoderms) responses. We show that the tlr3-like, tlr4-like, tlr6-like and tlr8-like transcripts are modulated by poly I:C, while LPS only modulates the tlr4-like response; there was no effect of temperature on TLR expression, as evaluated by RT-qPCR. Additionally, we showed that strongylocin-1 and strongylocin-2 are modulated in response to simulated viral infection with poly I:C, providing the first evidence of strongylocin expression in L. albus. Finally, we determined that temperature and LPS modify the viability of coelomocytes, while poly I:C treatment did not affect the viability of these cells. This study contributes to the knowledge of immune responses in sea urchins to improve the understanding of the role of TLRs and strongylocins in echinoderms. Highlights: Thermal stress decrease coelomocytes viability, with no effect in TLRs expression. LPS decrease coelomocytes viability at 8- and 12-h posttreatment. LPS stimulation increase in the tlr4-like expression at 2 h posttreatment. Poly I:C increase the tlr3-like, tlr4-like, tlr6-like and tlr8-like expression. Poly I:C induced expression of strongylocin-1 and strongylocin-2 on coelomocytes.